2011
DOI: 10.1055/s-0031-1273084
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Thrombosis Risk: Nutrients for Prevention of Thrombotic Disease

Abstract: An increased prothrombotic state is a major risk factor for the development of heart attacks, strokes, and venous thromboembolism. Platelet activation and aggregation play an important role in determining a prothrombotic state. Although pharmaceutical agents such as aspirin, heparin, and warfarin are able to reduce prothrombotic tendency, long-term drug treatment may produce a variety of side effects, including bleeding. Diet is generally recognized to be significantly involved in modifying the individual risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 116 publications
0
29
0
1
Order By: Relevance
“…Dietary supplements are widely used for improving the integrity and function of veins in the lower limbs, in order to increase the integrity of the tissue to improve the vein's function [47]. They also decrease the capillary's permeability by reducing the number and size of pores in the capillary's walls, improve the tone of or dilate the blood vessels and affect blood-clotting mechanisms [47]. In particular, we found that use of ginkgo showed a trend for a protective role in relation to CCSVI; however, because only 13% of participants answered this question, the data need to be confirmed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplements are widely used for improving the integrity and function of veins in the lower limbs, in order to increase the integrity of the tissue to improve the vein's function [47]. They also decrease the capillary's permeability by reducing the number and size of pores in the capillary's walls, improve the tone of or dilate the blood vessels and affect blood-clotting mechanisms [47]. In particular, we found that use of ginkgo showed a trend for a protective role in relation to CCSVI; however, because only 13% of participants answered this question, the data need to be confirmed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary flavonoids also include the anthocyanins cyanidin, delphinidin, malvidin, pelargonidin, peonidin and petunidin together with the flavanones hesperetin and naringenin, the flavones apigenin and luteolin, and the flavonols myricetin, kaempferol, and quercetin (Grotewold, 2006b). Apart from antioxidant activities, food-derived flavonoids were shown to reduce the incidence of atherosclerosis (Terao, 2009), cancer (Clere et al, 2011), cardiovascular diseases (Bojić, 2011), diabetes (Zheng et al, 2011), thrombosis (Phang et al, 2011), inflammation in arthritis (Gonzalez et al, 2011), neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases (Mandel et al, 2011), obesity (Birari et al, 2011), hyperlipidemia (Wang et al, 2011), nerve injury (Jäger and Saaby, 2011) and hypertension (Cassidy et al, 2011). …”
Section: Flavonoids As Nutraceuticalsmentioning
confidence: 99%
“…Nahrungsergänzungsmittel, welche eine hemmende Wirkung auf die Thrombozyten haben können (z. B. Gingko, [24]). Eine ebenfalls häufige Ursache einer Störung der primären Hämostase ist das (meist angeborene) Willebrand-Syndrom [19].…”
Section: Präoperative Gerinnungsdiagnostikunclassified